FACTORS AFFECTING COMPLIANCE WITH THE USE OF ANTI-RETROVIRAL DRUGS AMONG PERSONS LIVING WITH HIV/AIDS AT THE UNIVERSITY OF NIGERIA TEACHING HOSPITAL ENUGU, NIGERIA. (2013)
Anti-Retroviral (ARV) drugs are effective in reducing the incidence of death due to AIDS. The drugs are administered free of charge to People Living with HIV/AIDS (PLWHA) in designated clinics throughout Nigeria. Despite their availability compliance with ARV drug treatment remains a major challenge. The factors which influence compliance to ARV drugs among PLWHA in Nigeria have not been adequately studied. This research was therefore targeted at assessing the factors which affect compliance to ARV treatment among PLWHA at the University of Nigeria Teaching Hospital Enugu. A total of 341 consenting respondents out of the 1,200 patients who attended the weekly HIV clinic over a period of one month were selected for the study. A validated questionnaire which included questions on demographic characteristics, health related information, compliance with ARV, social support, counseling services, side effects, perceived benefits and inhibiting factors to ARV medication was used for data collection. Data were analyzed using descriptive statistics, Chi-square and logistic regression. Participants’ mean age was 36.8±9.8 years, 60.7% were females, 50.7% were married and 57.8% were traders/artisans. Respondents’ level of education was as follows: tertiary (31.1%), secondary (42.2%), primary (21.4%) and no formal education (5.3%). Many (48.4%) respondents’ had been on ARV treatment for 6 to 18 months preceding the study. Eighty three percent of the participants’ received counseling before they were placed on ARV drugs. An improvement in health was reported by 89.1% of those that took ARV drugs as prescribed. Seventy nine percent of the respondents fully complied with their ARV medication as prescribed. The reasons for failure to take the drugs as prescribed include traveling (19.1%), forgetfulness (17.3%) lack of access to food (7.9%). Forty percent of the respondents’ experienced side-effects after using the drugs; as a result of which 5.0% stopped using their drugs. The side-effects included: rashes (56.2%), diarrhea (30.7%), and abdominal pain (30.7%), vomiting (27.7%) and dizziness (24.8%). More males (82.0%) than females (77.3%) took their drugs as prescribed. Most (82.2%) of the married respondents took their drugs as prescribed compared to the singles (75.3%). Seventy nine point seven percent of the respondents within the age bracket 30 to 40 years complied with their ARV drug therapy whereas, 79.2% of those younger than 30 years and 78% of those older than 40 years took their ARV drugs as prescribed. Respondents who experienced improvements in their health status were more likely to comply with their treatment regimen than those who did not (OR= 15.2, 95% CI=1.6-140.1). The PLWHA who received social/ financial support were also more likely to comply with treatment regimen than those who did not receive social support (OR=1.8, 95% CI=1.1-3.1). Compliance to anti retroviral drugs was high among the respondents in spite of the attendant side effect. This positive health seeking behavior should be reinforced through effective health education strategy such as daily counseling and patient education.